Promoting the health and well-being of English-speaking Seniors in Quebec. A community model (infographic) - Community Health And Social Services Network/Réseau communautaire de santé et de services sociaux (2019)
fs-ref-orig: Community Health And Social Services Network. (2019). Promoting the health and well-being of English-speaking Seniors in Quebec. A community model [infographic]. fs-code-orig: Community Health And Social Services Network-2019

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 2 – Inventaire des services de santé disponibles en français et identification des déficits de services - De Moissac, Danielle; Ba, Halimatou; Gagné, Maryanne; Éthier, Sophie (Conseil communauté en santé du Manitoba, 2012)
Au Manitoba, des services de santé en français sont disponibles à Winnipeg, et plus précisément à Saint-Boniface et à Saint-Vital, où habite une forte concentration de francophones. L’objectif de ce deuxième volet de recherche sur l’accès des personnes âgées aux services de santé en français est de dresser un inventaire représentatif des services de santé publics, privés à but lucratif, privés à but non lucratif ou communautaires disponibles en français dans ces deux quartiers, pour ensuite identifier les déficits de services. On définit ici la disponibilité comme étant un service dont peuvent disposer les aînés et qui peut être utilisé par quiconque en fait la demande. Cet inventaire permettra de mieux connaître le nombre, le type et la nature des services existants et de déterminer si tous les services de santé et services sociaux disponibles en français sont répertoriés, soit dans l’Annuaire des services en français de la Société franco-manitobaine. Ceci est important, car une plus grande visibilité des services disponibles en français contribue grandement à leur utilisation par les aînés francophones et leurs aidants lorsque le besoin survient. De plus, l’inventaire permettra d’identifier le type et la nature des services manquants auxquels la population vieillissante pourrait avoir recours.

Identifying second language speech tasks and ability levels for successful nurse oral interaction with patients in a linguistic minority setting: An instrument development project - Isaacs, Talia; Laurier, Michel. D.; Turner, Carolyn. E.; Segalowitz, Norman (Health communication, 2011)
One of the most demanding situations for members of linguistic minorities is a conversation between a health professional and a patient, a situation that frequently arises for linguistic minority groups in North America, Europe, and elsewhere. The present study reports on the construction of an oral interaction scale for nurses serving linguistic minorities in their second language (L2). A mixed methods approach was used to identify and validate a set of speech activities relating to nurse interactions with patients and to derive the L2 ability required to carry out those tasks. The research included an extensive literature review, the development of an initial list of speech tasks, and validation of this list with a nurse focus group. The retained speech tasks were then developed into a questionnaire and administered to 133 Quebec nurses who assessed each speech task for difficulty in an L2 context. Results were submitted to Rasch analysis and calibrated with reference to the Canadian Language Benchmarks, and the constructs underlying the speech tasks were identified through exploratory and confirmatory factor analyses. Results showed that speech tasks dealing with emotional aspects of caregiving and conveying health-specific information were reported as being the most demanding in terms of L2 ability, and the most strongly associated with L2 ability required for nurse–patient interactions. Implications are discussed with respect to the development and use of assessment instruments to facilitate L2 workplace training for health care professionals.

Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux, 2019)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.

Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire( infographie) - Réseau communautaire de santé et de services sociaux/Community Health and Social Services Network (2019)
fs-ref-orig: Réseau communautaire de santé et de services sociaux. (2019). Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire [infographie]. fs-code-orig: Réseau communautaire de santé et de services sociaux-2019

Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Anglophone Magdalen Islanders, 2018)
fs-ref-orig: Richardson, M. et Ledoux, J.-J. (2018). Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes. Council for Anglophone Magdalen Islanders. fs-code-orig: Richardson-2018

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

L’impact d’un programme éducatif sur la qualité de vie de personnes aînées autonomes et hypertendues en milieu francophone minoritaire [thèse de maîtrise, Université d'Ottawa] - Taillon, Myriam (2016)
L’hypertension artérielle est une maladie chronique qui affecte près de 50 % des personnes de plus de 65 ans au Canada et de façon disproportionnelle, les communautés en situation minoritaire linguistique. L’objectif du projet était de sensibiliser des personnes de 65 ans et plus, hypertendues, en milieu francophone minoritaire aux facteurs de risque de l’hypertension par des ateliers éducatifs. L’impact de ces ateliers a été mesuré par un questionnaire sur la qualité de vie et des groupes de discussion. Il y a eu 34 participants. Les questionnaires ont révélé une amélioration dans les dimensions physique et mentale de la santé des participants (p < 0,001). Les groupes de discussion ont démontré que les participants comprenaient mieux la maladie et avaient modifié certains comportements. Les ateliers ont été reconnus comme très positifs par les participants. En conclusion, ce programme éducatif de 3 mois est efficace, faisable et apprécié chez cette population. Mots-clés hypertension artérielle, haute pression, francophone en situation linguistique minoritaire, personnes aînées, prise en charge, programme éducatif